Literacy Culture Development through Class Library at SDIT Salsabila 2 Klaseman Ngaglik Sleman - Ahmad Safi'i (Prodi PGMI IAIN Salatiga, 2019)
Life skills are proven to be able to improve human civilization. Improving literacy culture is one way to develop human life skills. The National Literacy Movement/ Gerakan Literasi Nasional (GLN) initiated by the government is an effort to realize it. SDIT Salsabila 2 Klaseman has a Class Literacy Movement/ Gerakan Literasi Kelas (GLK) program. The limited space available is not a reason to discourage GLK. This type of research was case study field research. The institution studied was SDIT Salsabila 2 Klaseman. The subjects consisted teachers, principals, students and parents. Data was obtained by observation, interviews and documentation steps. Analysis was performed by using data reduction techniques, data display, triangulation, and conclusion drawing/verification. The data showed that the main purpose of GLK was to intensify the culture of school literacy, library revitalization, and maintain the stability of school library functions. The technical implementation is by creating a class library in each class, fostering a sense of belonging to the class library, supplying books from the school library to the class library, providing educational playgrounds in the area of the class library, giving rewards for students who are diligent in reading, achievements are informed in public, and explore the student guardian support. The problems that arise are the lack of teacher exemplariness, lack of consistency, supply of books from school libraries is still small, and the system of re-education has not been orderly.